1993
DOI: 10.1021/bi00072a026
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of dendrotoxin K from black mamba, a potassium channel blocker

Abstract: Mamba dendrotoxins, 7K M(r) polypeptides with three disulfide bonds, selectively inhibit certain fast-activating, voltage-sensitive neuronal K+ channels and have been instrumental in their identification, localization, and purification. However, derivatives with more refined specificity are essential to define the structural and functional properties of the multiple subtypes known to reside in the nervous system. Hence, utilizing a constructed cDNA library from the venom glands of the black mamba (Dendroaspis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Multiple sequence alignments showed that mature SdPI shares homology with typical Kunitz-type venom peptides, including HWTX-XI from spider [7], kalicludine-1 from sea anemone [6], DTX-K from snake [8], and conkunitizin-S1 from cone snail [17]. The most homologous sequence HWTX-XI shows 52.7% identity to SdPI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sequence alignments showed that mature SdPI shares homology with typical Kunitz-type venom peptides, including HWTX-XI from spider [7], kalicludine-1 from sea anemone [6], DTX-K from snake [8], and conkunitizin-S1 from cone snail [17]. The most homologous sequence HWTX-XI shows 52.7% identity to SdPI.…”
Section: Resultsmentioning
confidence: 99%
“…Currently reported Kunitz-type venom peptides can be classified into two families based on different cysteine frameworks. One family retains the typical Kuntiz-type architecture, with three highly conserved disulfide bridges, exemplified by HWTX-XI from spider, DTX-K from snake, and kalicludines from sea anemone [6], [7], [8]. The other family has only four cysteine residues, which results in the apparent ‘loss’ of a conserved disulfide bridge, represented by conkunitzin-S1 from cone snail [9].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the cytoplasm, the periplasm of E. coli cells provides a relatively non-reducing environment that allows disulfide bridges to form [28]. It was reported that several peptide toxins, including Dendrotoxin K and Huwentoxin-XI, were functionally expressed in the periplasm of E. coli with the formation of disulfide bridges found in their natural forms [29], [30].…”
Section: Discussionmentioning
confidence: 99%
“…1). Hg1 and BmKTT-3 belong to the first group, which adopted classical disulfide pairings similar to HWTX-XI toxin from spider (20), dendrotoxin K from snake (32), and APEKTx1 from sea anemone (23). LmKTT-1a, LmKTT-1b, LmKTT-1c, and BmKTT-1 belong to the second group, which adopted a unique cystine framework that we described in our previous work (26).…”
Section: Primary Structures Of Scorpion Kunitz-typementioning
confidence: 95%